Endotoxaemia differentially regulates the expression of renal Ca2+transport proteins in mice - Meurer, Manuel; Höcherl, Klaus (Acta Physiologica, 2019)
Aim: Alterations in parathyroid hormone (PTH) and/or vitamin D signalling are frequently reported in patients with sepsis. The consequences on renal and intestinal Ca 2+ and P i regulatory mechanisms are still unclear. We hypothesized that endotoxaemia alters the expression of important renal and intestinal Ca 2+ and P i transport proteins. Methods: Male C57BL/6 mice were treated with lipopolysaccharide (LPS; 3 mg/kg; i.p.). The mRNA and protein levels of renal and intestinal Ca 2+ and P i transport proteins were measured by RT-qPCR, immunohistochemistry and western blot analysis. Results: Lipopolysaccharide-induced hypocalcaemia and hyperphosphataemia was paralleled by a decrease in glomerular filtration rate and urinary excretion of Ca 2+ and P i . Endotoxaemia augmented plasma levels of PTH and affected the fibroblast growth factor 23 (FGF23)-klotho-vitamin D axis by increasing plasma levels of FGF23 and downregulation of renal klotho expression. Renal expression of CYP27b1 and plasma levels of 1,25-dihydroxyvitamin D 3 were increased in response to LPS. Endotoxaemia augmented the renal expression of TRPV5, TRPV6 and PiT1, whereas the renal expression of calbindin-D 28K , NCX1, NaP i -2a and NaP i -2c were decreased. Incubation of primary distal tubule cells with LPS increased TRPV6 mRNA levels. Furthermore, LPS decreased the intestinal expression of TRPV6, calbindin-D 9K and of NaP i -2b. Conclusion: Our findings indicate that endotoxaemia is associated with hypocalcaemia and hyperphosphataemia and a disturbed FGF23-klotho-vitamin D signaling. Further, LPS-induced acute kidney injury was accompanied by an increased or decreased expression of specific renal and intestinal Ca 2+ and P i transporters respectively. It seems unlikely that LPS-induced hypocalcaemia is due to renal loss of Ca 2+ .
CRIS-Team Scopus Importer:2020-02-21
Keywords: acute kidney injury; calcium; inflammation; lipopolysaccharide; phosphate